2018
DOI: 10.2478/s11756-018-0073-y
|View full text |Cite
|
Sign up to set email alerts
|

Activity of beavers as an ecological factor that affects the benthos of small rivers - a case study in the Żylica River (Poland)

Abstract: The Eurasian beaver (Castor fiber) has a greater impact on local ecosystems than other herbivores, and the affected area exceeds the range of its presence. Its activity may change or create new habitats by modifying the availability of the biotic and abiotic resources available not only to beavers, but also to other groups of animals. Our aim was to study how beaver activity affects the benthos composition in a small river and in a beaver pond. The way in which beavers function in the case of small rivers has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Past studies on the effects of beavers on the density of macroinvertebrates have also found mixed results, with some studies reporting an increase in ponds and others a decrease (Anderson & Rosemond, 2010;Arndt & Domdei, 2011;Gard, 1961;Huey & Wolfrum, 1956;Law et al, 2016;McDowell & Naiman, 1986;Pliūraitė & Kesminas, 2012;Rolauffs et al, 2001;Rupp, 1955;Strzelec et al, 2018). However, the overall trend for all three streams was a higher average density in lotic reaches compared to beaver ponds.…”
Section: Biomass and Densitymentioning
confidence: 91%
See 4 more Smart Citations
“…Past studies on the effects of beavers on the density of macroinvertebrates have also found mixed results, with some studies reporting an increase in ponds and others a decrease (Anderson & Rosemond, 2010;Arndt & Domdei, 2011;Gard, 1961;Huey & Wolfrum, 1956;Law et al, 2016;McDowell & Naiman, 1986;Pliūraitė & Kesminas, 2012;Rolauffs et al, 2001;Rupp, 1955;Strzelec et al, 2018). However, the overall trend for all three streams was a higher average density in lotic reaches compared to beaver ponds.…”
Section: Biomass and Densitymentioning
confidence: 91%
“…Several studies have indicated a decrease in macroinvertebrate species richness within beaver ponds compared to lotic segments (Anderson & Rosemond, 2007;Arndt & Domdei, 2011;Gard, 1961;McDowell & Naiman, 1986;Pliūraitė & Kesminas, 2012;Strzelec, Białek & Spyra, 2018). Several studies have indicated a decrease in macroinvertebrate species richness within beaver ponds compared to lotic segments (Anderson & Rosemond, 2007;Arndt & Domdei, 2011;Gard, 1961;McDowell & Naiman, 1986;Pliūraitė & Kesminas, 2012;Strzelec, Białek & Spyra, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations